Multichannel Commerce: A Consumer Perspective on the Integration of Physical and Electronic Channels - Trenz, Manuel (Springer, 2015)
This book takes an in-depth look at consumer behavior in the context of multichannel commerce and explores how the convergence of physical and electronic channels influences consumer decision-making in a multichannel environment. In this regard, it goes far beyond explaining choices between online and offline sales channels, instead providing insights into how the interplay between different channel types is valued by different consumer types and for different products. The book extends previous conceptualizations of multichannel commerce to reflect and incorporate recent technological advances. The results provide valuable guidelines on how, why and when multichannel integration services can be exploited by classical retailers, helping them to compete with their purely online competitors on the internet.